Analysis of Hydrological Drought Events in the Upper Tana Basin of Kenya - Agwata, Jones F.; Wamicha, W. N.; Ondieki, Christopher N. (My University, 2015)
Drought is a major environmental hazard which has serious implications for water management and environmental protection. This is especially so when unsustainable water management, as well as predicted climate change effects in droughts, could result in severe impacts on nature and society. Inefficient management of drought and water resources could put aquatic ecosystems under serious severe stress. The lack of adequate water availability in rivers during drought episodes leads to heavy overexploitation of the rivers and reservoirs, which significantly affects the survival of associated biological diversity. It is therefore essential to know the occurrence of drought events in river basins with a view to establishing and developing measures to minimize the socioeconomic and environmental impacts of its effects in these areas. In this paper, drought duration and severity were examined in four homogenous regions of the upper Tana basin. The homogenous regions were established using principal component analysis results of discharge data from twenty two river gauge stations in basin. The runs analysis technique was then applied to examine the drought duration and severity at the homogenous regions of the basin. Results indicated that the mean drought duration varied from 4 to 11 months across the regions whilst the standardized mean severity ranged from 0.63 to 3.89. Two of the regions experienced nearly the same standardized mean severity. Drought events occurred at times when the basin experienced rainfall deficits an indication that low rainfall affects discharge in the rivers of the basin. The variations in the number and frequency of the drought events in the homogenous regions would possibly be related to the semi-arid and arid nature of the climate in most of the southern and eastern parts of the basin. To minimize the impacts of drought in the basin, it is recommended that capacity building of the local communities in the basin be done focusing on water conservation and alternative livelihoods systems to minimize overdependence on water resources in the basin.
Keywords: Drought; Hydrological drought; Runs analysis; Water management